Bigger than life [videorecording (DVD)] - Ray, Nicholas, 1911-1979; Mason, James, 1909-1984; Rush, Barbara, 1927-; Matthau, Walter; Roueché, Burton (Criterion collection (DVD videodiscs), 2010)
A friendly suburban teacher becomes addicted to cortisone, turning the normally gentle husband and father into a psychotic despot.